Advanced emulsions via noncovalent interaction-mediated interfacial self-assembly. Issue 25 (12th March 2018) - Han, Songling; An, Huijie; Tao, Hui; Li, Lanlan; Qi, Yuantong; Ma, Yongchang; Li, Xiaohui; Wang, Ruibing; Zhang, Jianxiang
Abstract : The traditional emulsification theory is enriched by a self-assembly approach, in which hydrophilic copolymers with one block exhibiting electrostatic or hydrogen-bonding forces with the oil phase self-assemble at the oil–water interface, thereby reducing interfacial tension and forming emulsions. Abstract : We demonstrate that the traditional emulsification theory can be enriched by a self-assembly approach, in which hydrophilic copolymers with one block exhibiting noncovalent forces with the oil phase self-assemble at the oil–water interface, thereby reducing interfacial tension and forming emulsions. This approach was established using affinity diblock copolymers that can interact with oil molecules through electrostatic interactions or hydrogen-bonding. Nanoemulsions with excellent stability were successfully obtained simply via vortexing. The self-assembled emulsions showed unexpected catastrophic phase inversion, further extending the phase structures to bicontinuous and reverse emulsions. Complex emulsions could also be fabricated by this strategy. In addition, the thus prepared nanoemulsions can be used to engineer different nanomaterials.